Approximation of symmetrizations and symmetry of critical points - Van Schaftingen, Jean (Topological Methods in Nonlinear Analysis, 2006)
We give a sufficient condition in order that a sequence of cap or Steiner symmetrizations or of polarizations approximates some fixed cap or Steiner symmetrization. This condition is used to obtain the almost sure convergence for random sequences of symmetrization taken in an appropriate set. The results are applicable to the symmetrization of sets. An application is given to the study of the symmetry of critical points obtained by minimax methods based on the Krasnosel’skiĭ genus.